2011
DOI: 10.1007/s13340-011-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Validity and applicability of a simple questionnaire for the estimation of total and domain-specific physical activity

Abstract: Purpose We developed and evaluated a simple, robust and valid self-administered questionnaire for the estimation of physical activity (PA). Here, we examined the validity of this questionnaire in subjects with differing sex, ages, occupations and living circumstances. Methods The questionnaire consists of four domains, namely occupational activity, including housekeeping and commuting; leisure time activity; sleeping; and other activities. It was validated with 8-day, 24-h physical activity records (24 h-R) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…A previous study showed that implementation of 24-h PA records could be complicated by the need to record PA for several days [37]. The JPHC-PAQ Long was established to provide a valid estimation of total PA (METs) in comparison to 24-h PA records for 8 days among a slightly younger population (mean age 60.7 years) than the subjects in the present study [30]. Although this questionnaire was not originally designed to estimate energy expenditure, a recent study demonstrated the validity of the questionnaire for estimating TEE (compared with the DLW method) in a younger population [11].…”
Section: Discussion/conclusionmentioning
confidence: 86%
See 2 more Smart Citations
“…A previous study showed that implementation of 24-h PA records could be complicated by the need to record PA for several days [37]. The JPHC-PAQ Long was established to provide a valid estimation of total PA (METs) in comparison to 24-h PA records for 8 days among a slightly younger population (mean age 60.7 years) than the subjects in the present study [30]. Although this questionnaire was not originally designed to estimate energy expenditure, a recent study demonstrated the validity of the questionnaire for estimating TEE (compared with the DLW method) in a younger population [11].…”
Section: Discussion/conclusionmentioning
confidence: 86%
“…Physical Activity Questionnaire Subjective PA in the past year was evaluated by recall using the Japan Public Health Center-based Prospective Study-PAQ long form (JPHC-PAQ Long) [30]. This questionnaire consists of 4 domains, namely, occupational activity: sitting (1.5 METs), standing (2.0 METs), walking (2.0 METs), and strenuous work (4.0 METs); leisure time activity: walking slowly (3.0 METs), walking fast (4.0 METs), light to moderate exercise (4.0 METs), and vigorous activity (4.5 METs); other activities (1.5 METs); and sleeping (0.9 METs).…”
Section: Physical Activity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Total PA was determined by summing the three categories of activity and by multiplying the hours spent in each activity by the assigned MET value. The PA survey administered to TMCS participants was developed initially for the Japan Public Health Center-based Study [102] and relies on measurement of the domains of occupational activity, leisure time activity, sleeping, and other activities [103]. Total PA was determined by summing all domains of activity and by multiplying the hours spent in each activity by the assigned MET value.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…BMI was calculated by dividing weight (kg) by height squared (m 2 ). Physical activity levels were assessed by determining participant metabolic equivalent (MET) score (MET-h/d), obtained by multiplying the time score spent with activities by its MET intensity (16) . Time spent outdoors per d in the last week (<20, 20-39, 40-59, 60-179 and ≥180 min/d) and sunscreen use were determined.…”
Section: Baseline Examinationmentioning
confidence: 99%